2019
DOI: 10.1002/ptr.6489
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrae Chinensis Fructus inhibits behavioral deficits induced by sleep deprivation and chronic unpredictable mild stress via increased signaling of brain‐derived neurotrophic factor

Abstract: The present study was undertaken to explore the interactions between sleep deprivation (SD) and Schisandrae Chinensis Fructus (SCF) treatment in the antidepressant‐like effects. We observed that SD aggravated the anxiety‐like behavior induced by chronic unpredictable mild stress (CUMS) in the elevated plus maze test. However, the forced swimming test and sucrose preference test showed that SD (12 hr) alleviated the depressive symptoms and SD (72 hr) has the opposite effects. Administration of SCF showed a prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…Considering that the main subcortical input of hippocampus is from the medial septum of the basal forebrain cholinergic system (Solari & Hangya 2018) and the septo‐hippocampal pathway, the main projection of medial septal neurons (Everitt & Robbins, 1997), is also important for processing of aversive information during fear conditioning (Calandreau, Jaffard, & Desmedt, 2007; Stepanichev, Lazareva, Tukhbatova, Salozhin, & Gulyaeva, 2014), there might be a possibility that sleep deprivation‐induced increase in basal forebrain BDNF might activate basal forebrain cholinergic neurons which further increased hippocampal BDNF expression and fear memory consolidation. Although recent research showed BDNF level in hippocampus was elevated by 12‐hr sleep deprivation (Yan et al, 2019), whether BDNF/TrkB (Y816)/ PLCγ(Y783) signaling in hippocampus was activated after sleep deprivation needs further confirmation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering that the main subcortical input of hippocampus is from the medial septum of the basal forebrain cholinergic system (Solari & Hangya 2018) and the septo‐hippocampal pathway, the main projection of medial septal neurons (Everitt & Robbins, 1997), is also important for processing of aversive information during fear conditioning (Calandreau, Jaffard, & Desmedt, 2007; Stepanichev, Lazareva, Tukhbatova, Salozhin, & Gulyaeva, 2014), there might be a possibility that sleep deprivation‐induced increase in basal forebrain BDNF might activate basal forebrain cholinergic neurons which further increased hippocampal BDNF expression and fear memory consolidation. Although recent research showed BDNF level in hippocampus was elevated by 12‐hr sleep deprivation (Yan et al, 2019), whether BDNF/TrkB (Y816)/ PLCγ(Y783) signaling in hippocampus was activated after sleep deprivation needs further confirmation.…”
Section: Discussionmentioning
confidence: 98%
“…It is tempting to relate the preservation of fear memory with the increased BDNF levels seen in the sleep deprived rats. Indeed, brain adaptive response after acute sleep deprivation has been confirmed in gene expression (Cirelli, Gutierrez, & Tononi, 2004), neurotransmitter release (Dash, Douglas, Vyazovskiy, Cirelli, & Tononi, 2009), and compensatory recruitment of different brain structures, such as hippocampus (Yan et al, 2019). In this context, and considering the pivotal functions of BDNF in memory consolidation, elevation of transcription of BDNF during acute sleep deprivation could play a modulating role of the fear memory process.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, CUMS inhibited BDNF/TrkB/ERK/CREB signaling pathway, which was in accordance with the previous studies. [ 35–37 ] In contrast, chronic porphyran administration for 4 weeks reversed the inhibition of BDNF/TrkB/ERK/CREB pathway. Besides the neurotrophic signaling, we also evaluated the effects of porphyran on neurogenesis and spinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…After these new neurons are generated, they proliferate, migrate, and differentiate and are subsequently integrated into the existing neuronal circuits to form synaptic connections [ 11 ]. Brain-derived neurotrophic factor (BDNF) is widely distributed in the brain and plays an important role in the survival, development, and growth of central neurons [ 12 ] and is involved in the regulation of neurogenesis [ 13 ]. Decreased BDNF levels and abnormal neurogenesis are associated with depressive symptoms and behaviors [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%